Enlarging flexibility region of virtual power plant via dynamic line rating. Issue 4 (15th February 2022) - Tan, Zhenfei; Wang, Siyu; Zhong, Haiwang; Xia, Qing; Kang, Chongqing
Abstract: The virtual power plant (VPP) can aggregate small‐scale distributed resources to provide flexibility for the transmission system. The flexibility provision capability of the VPP is restricted by technical operating limits of the distribution system to which distributed resources are connected. To facilitate the flexibility provision of the VPP while securing the operation of the local system, this paper leverages the dynamic line rating (DLR) to enlarge the VPP flexibility region. The flexibility region of the VPP is defined as the allowable range of active and reactive power output that the VPP can execute subject to operating constraints of the internal system. With the DLR, the current carrying capacity of the distribution network is dynamically adjusted based on actual environmental conditions, which helps to remove barriers from transmission limits that hinder the integration of distributed flexibility. A convex hull‐based method with an explicit accuracy guarantee is proposed to approximate the flexibility region with the DLR. Case studies based on IEEE‐33 and IEEE‐123 test feeders with real‐world operation data validate the proposed framework.